IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN BALIK ALAM KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2020 - Muhammad Afriyandi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the implementation of the City Without Slum (KOTAKU) program in Balik Alam Village, Mandau District, Bengkalis Regency in 2020. This study uses the theory of policy implementation proposed by George C. Edward III, namely communication, resources, disposition and structure. This research uses a descriptive approach with a qualitative research type. Then the data collection techniques used are interviews, observation, and documentation. While the data analysis technique is done by collecting information through interviews, data reduction and data presentationThe results of this study indicate that the implementation of the City Without Slum Program in the Balik Alam Village, Mandau District, Bengkalis Regency in 2020 is quite good because it has fulfilled all the factors or variables proposed by George C. Edward III. Good and effective communication, adequate resources, human resources, equipment resources and resources, attitude of implementers who are able to run optimally, and very clear structure of mechanisms and systems. Keywords: Policy, City Without Slum program, Resources